A queueing model for a terminal system subject to breakdowns - Sztrik, J.; Gál, T. (Computers & mathematics with applications (1987), 1990)
The queueing system to be analysed is a model of a terminal system subject to random breakdowns. All random variables involved here are independent and exponentially distributed. Although, the stochastic process describing the system's behaviour is a Markov chain, the number of states becomes very large. Therefore, our aim is to give a recursive scheme for the solution of the steady-state equations. In equilibrium, the main performance measures of the system, such as mean number of jobs staying at the CPU, the mean number of good terminals, the average number of busy servers, the expected response times of jobs, and utilizations are obtained. Finally, some numerical results illustrate the problem in question.